Theoretical Landscapes of the Anthropocene - Biset, Emmanuel (2025)
In this paper, I seek to delineate the recent post-textual direction of theory. To this end, the text undertakes two key  moves: firstly, it articulates a connection between Fredric Jameson’s concept of cognitive map and Anna Tsing’s concept of the atlas. Secondly, it identifies three indicators of shifts in theoretical discourse: the move away from the linguistic turn, the critique of human exceptionalism, and the debates surrounding Kantian mediation. After analysing the general aspects of a contemporary theoretical map, it demonstrates how certain political discussions emerge from it. In short, the aim of the text is to provide an account of certain guidelines that enable theoretical orientation.